Validity and Reliability of Knowledge, Attitude and Practice Questionnaire of Ear Care among Medical Workers - Arsyada Hakama Syakuro; Deoni Daniswara; Adnan Abdullah; Rizka Fakhriani; Asti Widuri (Ahmad Dahlan Medical Journal, 2024)
The auditory system is a vital and prominent component of human. It is imperative for individuals to prioritize the maintenance of this organ throughout their lives. These methods encompass the maintenance of ear cleanliness, safeguarding against excessive noise exposure, preventing accidents, and warding off ear infections and disorders. The aim of this study was to determine the validity and reliability of knowledge, attitude, and practice about ear care among medical workers. This study uses a descriptive-analytic method with a cross-sectional design. The ear care questionnaire comprising of knowledge, attitude and practice translated and applicated for 45 participants, the validity test using Pearson’s correlation and reliability test evaluation determined by Cronbach’ s alpha. The ear care questionnaire Indonesian version found Pearson’s correlation of all items r above 0.35 or strongly valid, and the Cronbach’s alpha coefficient was 0.749 (adequate). Indonesian version of knowledge, attitude, and practice about ear care is valid and reliable, the result of assessment can indicate the needed of public awareness through education and health promotion.